THE BODY, MORALITY AND COMMUNITY LIFE: A NURSING HOME PERSPECTIVE (Fiep Bulletin - online, 2014)
The present article is a result of research begun in 2006 at the Vila Vicentina Júlia Freire elderly care facility in João Pessoa, Brazil. The purpose of the study was to observe the behaviors of the residents in terms of their social life, socialization and way of life, focusing on their body image. The methodology used was the narrative interview, whose finality was to follow their thinking from childhood to the present in order to give us an idea of how they see the world and each other. Within these narratives is the way in which they deal with sexuality and the types of relationships formed between their peers as well as the natural conflicts arising from these bonds. The residents of the Vila have loving relationships, get married and base their values on the individual experiences of each one. Valuing body image becomes an almost instinctive attitude, given the care that the men and women take of their appearance and the concern about what the others think of them.
Keywords: old age; sexuality; quality of life